متطلبات إدارة الموارد البشرية وصعوباتها في شركات التطوير العقاري العامة في والخاصة سورية - علي, علي محمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
This research highlights the need to activate the role of human resources management in these companies and the importance of applying practices that lead to improving the efficiency of human resources management by creating a qualified, capable and willing workforce to achieve the objectives pursued by companies. As the human resources management is particularly important in the Syrian public and private real estate development companies, this research aims to study the importance of human resource management in the Syrian public and private real estate development companies. The field study was conducted on a representative sample of 7 companies of public and private real estate companies. The main results of the research were the poor performance of human resources departments and their non-application of scientific standards in the analysis of jobs in public and private companies. Recruitment and selection procedures were limited recruitment in public companies to rotate the employment between divisions of the company, while employment is broadly recruited from the labour market for private companies. Recruitment and selection procedures in public companies depended on general competitions where previous experiences and skills acquired were not taken into consideration, while recruitment and selection procedures in private sector companies rely on strict criteria for professional employment, public companies merely perform routine periodic evaluation every two years, while private companies have ongoing assessment of employees at the end of each project. The Search recommended to activate the role of human resource management. يسلط البحث الضوء على أهمية تطبيق الممارسات التي تؤدي إلى رفع كفاءة إدارة الموارد البشرية، فكان الهدف دراسة متطلبات إدارة الموارد البشرية وصعوباتها في شركات التطوير العقاري العامة والخاصة في سورية. اعتمد البحث على المنهج الوصفي التحليلي كمنهج عام للدراسة، واستخدم برنامج Spss20 لتحليل الاستبيان. تمثل مجتمع البحث بالعاملين في شركات التطوير العقاري الخاصة العاملة في سورية بلغ عددها 39 شركة. اعتمد الباحث إجراء المقابلات الشخصية مع بعض أفراد عينة الدراسة. وكانت أبرز نتائج البحث ضعف أداء أقسام الموارد البشرية وعدم تطبيقها للمعايير العلمية في تحليل الوظائف، اقتصر الاستقطاب في الشركات العامة على تدوير العمالة بين أقسام الشركة، بينما يتم الاستقطاب بشكل واسع من سوق العمل للشركات الخاصة، اعتمدت إجراءات التعيين والاختيار في الشركات العامة على مسابقات تعيين عامة، بينما تعتمد شركات القطاع الخاص على معايير صارمة خاصة للعمالة الفنية، وتكتفي الشركات العامة بالتقييم الدوري الروتيني كل عامين، بينما الشركات الخاصة لديها تقييم مستمر للعاملين بنهاية كل مشروع.